Síndrome vestibular em Lithobates catesbeianus associada à ranavirus - Mesquita, Adriano Queiroz de (2014)
Frog farming is an expanding activity in South America. In Brazil it can be considered consolidated, especially in the state ofGoiás. In the last few years it turned into a superintensive activity and consequently favored the emergence of diseases that pose a threat to the technical and economic viability of farms of aquatic organisms. Several diseases with high morbidity and mortality have been observed in tadpoles and frogs. Especially in the state of Goiás, two diseases affect the production cycle in the frog farms. The first manifests itself in 30 days tadpoles leading to high mortality and has been associated to the presence of Ranavirus. The second affects frogs in all stages from post-molt to the point of slaughtering. In post-metamorphic phase the animals are cachectic and 10-50 % of the populationdevelops nervous signs such as incoordination and abnormal postures chronic condition. Despite the board's neurological symptoms, some frogs are able to feed and continue to grow slowly, with few recovering normal condition. This clinical manifestation may be attributed to the anatomy of the vestibular system and hearing. Afferent bilateral vestibular signals from semicircular canal and otolith organs are essential for the stabilization of gaze, the control of posture and locomotion as well as the cognitive aspects of balance, spatial orientation and vegetative homeostasis. Considering the relevance of the topic, the objective of this study is to contribute to the elucidation of Vestibular Syndrome in Rana catesbeiana focusing in the presence of Ranavirus through the use of methods of diagnosis and histopathological techniques , real-time PCR , immunohistochemistry and electron microscopy. In the first study, we developed a method of detecting Ranavirus by real-time PCR for diagnosis of clinically healthy and diseased frogs with nerve signals in order to monitor the spread of this agent for this and other species of animals that inhabit the frog farms around the state of Goiás 91 samples were collected randomly frog farms in the countryside of the stateof Goiás of these, 50 were from frogs without clinical symptoms and 41 box of frogs with nerve sequelae characterized by lack of coordination , posture with abnormal lordosis, scoliosis and various degrees of head tilt to the left or right side. Based on these results, it is concluded that the frequency of ranavirus frogs with neurological symptoms is higher than the frequency of ranavirus frogs without apparent clinical symptoms, indicating association of clinical findings with the presence of the virus. The detection of ranavirus in animals living near the frog farms in the state of Goiás indicates that the virus is spread in the sampled detection in fish and frog farms reveals need for monitoring thespread of the virus to prevent cases of mass mortality in other species. In the second study, samples were collected randomly from 60 bullfrogs from frog farms in the state of Goiás in order to identify the agent involved in chronic, vestibular syndrome similar to clinical problems through diagnostic techniques such as transmission electron microscopy, histopathology and immunohistochemistry. Of these, 30 bullfrogs had typical clinical picture and 30 bullfrogs had become asymptomatic. At histopathology, inflammatory type of lesions with necrosis and lymphocytic infiltration were seen in the posterior regions of the cerebrum and cerebellum, with meningoencephalitis and inclusion bodies, areas of gliosis, and necrotic foci with abundant macrophages and cellular debris associated with inflammatory infiltrates. The choroid plexus showed abundant inflammatory infiltrates and lesions similar to those described above. Theselesions were also observed in the region of the semicircular canals and the central and peripheral vestibular apparatus to the front and cross cuts. These specimens subjected to staining with specific anti - iridovirus revealed the presence of positive staining in the choroid plexus region. This finding associated with the lesions described in anatomohistopatologia confirms the presence of Ranavirus. When analyzing the images obtained by electron microscopy transmission of samples from kidney and liver of bullfrog it was possible to visualize viral particles with similar characteristics to that of ranavirus, with icosahedral symmetry and size ranging from 120 - 300nm . Thus, it is concluded that the lesions of inflammatory type, described in anatomohistopatologia in the posterior central nervous system bullfrogs region, extending to the middle and inner ear, nervous symptoms associated with vestibular character indicate the presence of Ranavirus. Regarding immunohistochemistry, the presence of positive staining with specific anti- Iridovirus in the affected cells of the choroid plexus of bullfrog, associated to lesions described in anatomohistopatologia region confirms the presence of ranavirus and the presence of viral particles in the liver and kidney bullfrog, associated with inflammatory lesions in the posterior type central nervous system region, extending to the middle and inner ear, described in the present study also confirms the presence of Ranavirusin frog farms of the state of Goiás.